Analysis of Expected Costs of Carpal Tunnel Syndrome Treatment Strategies. (May 2019) - Milone, Michael T.; Karim, Adnan; Klifto, Christopher S.; Capo, John T.
Background: Over 500 000 carpal tunnel releases costing over 2 billion are performed each year in the United States. The study's purpose is to perform a cost-minimizing analysis to identify the least costly strategy for carpal tunnel syndrome treatment utilizing existing success rates based on previously reported literature.Methods: We evaluate the expected cost of various treatment strategies based on the likelihood of further treatments: (1) a single steroid injection followed by surgical release; (2) up to 2 steroid injections before surgical release; (3) 3 steroid injections before surgery, and (4) immediate surgical release. To reflect costs, we use our institution's billing charges to private payers and reimbursements from Medicare. A range of expected steroid injection success rates are employed based on previously published literature.Results: Immediate surgical release is the costliest treatment with an expected cost of 2149 to 9927 per patient. For immediate surgical release to cost less than a single injection attempt, the probability of surgery after injection would need to exceed 80% in the Medicare reimbursement model and 87% in the institutional billing model. A single steroid injection with subsequent surgery, if needed, amounts to a direct cost savings of 359 million annually compared with immediate surgical release. Three injections before surgery, with "high" expected success rates, represent the cost-minimizing scenario.Conclusions: Although many factors must be considered when deciding upon treatment for carpal tunnel syndrome, direct payer cost is an important component, and the initial management with steroid injections minimizes these direct payer costs.